Penggunaan Media Damas untuk Meningkatkan Karakter dan Hasil Belajar Siswa Kelas 1 SD Negeri Sen Asen 1 - Ardiyansah Yuliniar Firdaus (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2019)
This study uses a classroom action research design model Kemmis and Taggart which aims to improve the character and student learning outcomes through the use of media damas in Mathematics. The subjects of this study were the first grade students of Elementary School State 1 Sen Asen. Data collection techniques were carried out through observation and tests which were then analyzed descriptively quantitative. The results showed that the media of damas can improve: 1) the character of students marked by an increase in cycle I with a percentage of 64.2% (good criteria) increased to 82.5% (very good criteria) in the second cycle; 2) student learning outcomes are characterized by a classical increase in cycle I with a percentage of 65% (13 students) increasing to 95% (19 students) in cycle II. So it can be concluded that use of damas media can improve the character and student learning outcomes.